Child Marriage, Early Childbearing, Low Educational Attainment for Girls, and Their Impacts in Uganda - Wodon, Quentin (World Bank, Washington, DC, 2017)
The proportions of girls marrying or having children before the age of 18 have been declining in Uganda according to data from the latest publicly available Demographic and Health Survey (DHS) implemented in 2011. Yet despite progress, more than one third of girls still marry as children, and close to three in ten girls have their first child before turning 18. Similarly, despite substantial efforts to improve educational attainment, only one in four girls completes lower secondary school, and an even smaller proportion completes upper secondary school. The government of Uganda has adopted a national strategy to end child marriage and teenage pregnancies. Improving girls’ education is also a priority of the government. Unfortunately, the cultural, economic, and social conditions that have historically contributed to child marriage, early childbearing, and low educational attainment for girls remain strong. More needs to be done to accelerate progress. To inspire greater investments in adolescent girls, this note analyses the economic and social impacts of these issues in Uganda. The note also suggests potential options for investments.